2017
DOI: 10.5812/ijcm.7644
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Early and Late Complications in Three Esophagectomy Techniques

Abstract: Background: Due to the high prevalence and mortality rates of esophageal cancer in some parts of the world and considering that in most patients, symptoms occur when cancer is advanced, this study aimed to compare early and late complications in three esophagectomy techniques for treatment of esophageal cancer. Methods: The present study was a descriptive research on 316 patients with esophageal cancer referring to Shohada Tajrish hospital, Tehran. The results were recorded in the research forms consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Until achieving this success, transhiatal esophagectomy is a suitable option for old, smoker, and malnourished patients with several comorbidities. The present study and experiences (1,2,10,11) indicated that non-radical surgery such as the Orringer technique is acceptable and compassable with radical esophagectomy.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Until achieving this success, transhiatal esophagectomy is a suitable option for old, smoker, and malnourished patients with several comorbidities. The present study and experiences (1,2,10,11) indicated that non-radical surgery such as the Orringer technique is acceptable and compassable with radical esophagectomy.…”
Section: Discussionsupporting
confidence: 53%
“…Transhiatal esophagectomy (Orringer technique) is done through 2 incisions, 1 at the neck and the other at the abdomen, only lower mediastinal lymph nodes can be removed (1,11,12). This technique was associated with low mortality and morbidity in more extensive studies but with no survival difference (1,2,10,12). Mortality and morbidity in our series were lower than in its original series (3.5% vs. 4%) (11) perhaps due to technical and experimental issues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations